Droga do sukcesu ekonomicznego Unii Europejskiej - Jaworska, Maria (The Way to the Economic Success of the European Union, 2008)
Economic success means the highest level of socio-economic development and financial prosperity of society. Achieving such an effect in economy is possible thanks to restructuring. Putting emphasis on knowledge and R&D zone is currently a basis for economic development, creating professions as well as raising life standard. Information and communication technologies determine the strategic direction of developmental expansions
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 283-299